Exercise and mitochondrial health. (9th December 2019) - Memme, Jonathan M.; Erlich, Avigail T.; Phukan, Geetika; Hood, David A.
Abstract: Mitochondrial health is an important mediator of cellular function across a range of tissues, and as a result contributes to whole‐body vitality in health and disease. Our understanding of the regulation and function of these organelles is of great interest to scientists and clinicians across many disciplines within our healthcare system. Skeletal muscle is a useful model tissue for the study of mitochondrial adaptations because of its mass and contribution to whole body metabolism. The remarkable plasticity of mitochondria allows them to adjust their volume, structure and capacity under conditions such as exercise, which is useful or improving metabolic health in individuals with various diseases and/or advancing age. Mitochondria exist within muscle as a functional reticulum which is maintained by dynamic processes of biogenesis and fusion, and is balanced by opposing processes of fission and mitophagy. The sophisticated coordination of these events is incompletely understood, but is imperative for organelle function and essential for the maintenance of an interconnected organelle network that is finely tuned to the metabolic needs of the cell. Further elucidation of the mechanisms of mitochondrial turnover in muscle could offer potential therapeutic targets for the advancement of health and longevity among our ageing populations. As well, investigating exercise modalities that are both convenient and capable of inducing robust mitochondrial adaptations are useful in fostering more widespread global adherence. To this point, exercise remains the most potent behavioural therapeutic approach for the improvement of mitochondrial health, not only in muscle, but potentially also in other tissues. Abstract : Abstract figure legend The mitochondrial life cycle is regulated by the finely tuned balance of biogenesis and fusion, opposed to fission and mitophagy. At any moment these processes are in a state of flux and are induced and/or suppressed depending on the status of the cell and the physiological conditions it is subjected to. A hallmark feature of aged muscle is the reduction of both subsarcolemmal (SS) and intermyofibrillar (IMF) mitochondrial fractions, determined by a thinner SS mitochondria layer (yellow arrow) and fragmented IMF pool, as compared to their younger counterparts. Additionally, aged muscle presents an accumulation of damaged mitochondria (green organelles). Physical activity is a well‐established inducer of mitochondrial remodelling that promotes increases in both SS layer thickness as well as IMF interconnectivity. Additionally, aged muscle is capable of adapting to the exercise stimulus which improves mitochondrial content and quality. Indications of a mitochondrial contribution to sarcopenia suggest that, with regular exercise, mitochondrial health can be preserved well into old age and contribute to whole body vitality.